Understanding Forgiveness After Leaving an Abusive Relationship: The Voices of Chinese Female Intimate Partner Violence Survivors - Wu, Qinglu (Violence against women, 2021)
Forgiveness is known to play an important role in recovery studies of female intimate partner violence (IPV) survivors. However, survivors’ understanding of forgiveness remains unclear. This study explored forgiveness through semi-structured interviews with 25 Chinese women. The results indicate that forgiveness is an unintended process that comprises the alleviation of a grudge held against former partners and a reframed understanding of them. It does not involve reconciliation. Moreover, establishment of clear boundaries is a precondition for forgiveness. The findings supplement knowledge on forgiveness and the importance of cognitive reframing, emotion regulation, and establishing clear boundaries in forgiveness and recovery.